Little women - Alcott, Louisa May (New York, 1983)
Meg, Jo, Beth, and Amy don't have a lot of money, but they are rich in love. Will that be enough to see the sisters through? -- back cover.
Keywords: Family life--New England--Fiction; Sisters - Fiction